Industrial property management in manufacturing enterprises – an attempt to construct a definition of the concept for use within management sciences - Wojtkiewicz, Monika (Zarządzanie własnością przemysłową w przedsiębiorstwach produkcyjnych – próba konstrukcji definicji pojęcia na użytek nauk o zarządzaniu, 2021)
The purpose of this article is an attempt to define the concept of industrial property management based on literature research and the author’s own conceptual work devoted to the problem of defining this area. As a result of the conducted analyses, the author concludes that the hitherto and inconsistent interpretations of the notion of industrial property, as well as their detachment from management sciences, and giving them a character proper to legal sciences, gives rise to significant problems in the understanding and implementation of management processes in this area, and more importantly, also in the understanding of the importance and significance of this area for the proper management of a manufacturing enterprise. The author presents the view that the concept of industrial property must be understood more extensively in management sciences and, at the same time, broadly enough to allow for an unambiguous definition of industrial property management that would serve its stakeholders in a key way that does not raise any substantial doubts.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 62-81
Keywords: industrial property; industrial property management; intellectual property resources; company innovation potential; innovation; własność przemysłowa; zarządzanie własnością przemysłową; zasoby własności intelektualnej; potencjał innowacyjny przedsiębiorstwa; innowacje